Examining the capacity of a sport for development programme to create social capital. Issue 3 (4th March 2018) - Adams, Andrew; Harris, Kevin; Lindsey, Iain
Abstract: Robert Putnam's conceptualization of social capital has been commonly associated with, and used to analyse, sport-for-development programmes. This paper bucks this trend and uses James Coleman's rational strain of social capital to examine the use of sport as a component part of a programme to support male adults in addressing connected problems of substance misuse, homelessness and other forms of social exclusion. Using a qualitative research strategy, in-depth and longitudinal data were collected using individual interviews and focus groups with programme participants and key stakeholders over a three-year period. The results suggest the importance of unintentionality for the formation and use value of social capital; indicating that social capital created through this programme was individual, contingent on interactional context and benefited individuals in line with Coleman's six aspects of social capital.